An analysis of learning preferences of Mechanical Engineering undergraduate students at Universiti Teknologi Mara (UiTM) Pulau Pinang to improve teaching approach / Salina Budin and Shaira Ismail - Budin, Salina; Ismail, Shaira (2014)
Students learn effectively in a preferable learning environment with suitable teaching approach that matches their learning preferences. Teaching and learning activities which suit students’ learning preferences have an impact on their motivational level to learn. As for the lecturers, it will help lecturers to organize and improve their teaching aids, learning and teaching assessment and learning environment. This work aims to analyze the learning preferences among the Diploma students in the Faculty of Mechanical Engineering which can be used to improve teaching approaches. The Dunn and Dunn Learning Styles model consists of five elements namely; environmental, sociological, emotional, physiological and psychological is applied in the survey involving of 131 students. The results show that, the diploma students of Mechanical Engineering posses various learning preferences. For the learning environmental element, majorities are more convenient in cool environment with informal seating design. Whereas for sound background and lighting elements, the students are nearly well balance distributed. Equilibrium distribution of learning preferences is also seen in the emotional element. For the sociological aspect, most of the students chose variations which indicate that, they are able to adapt their learning styles either self, pair, peers or team. Physiological aspect reflects that most of the students are visual learners, morning alert and requires of having snack during classes. They are also hardly to remain seated for a certain period of time. Finally, from the psychological aspect, most of them are analytical learners, left-brain dominants with reflective learning styles. The research outcomes will help lecturers to develop a variety approach in improving teaching and learning activities in order to align with students learning preferences. Consequently, it will improve the teaching approach and enhance the transfer of learning.